Fatal recurrence of fulminant giant cell myocarditis and recovery after initialisation of an alternative immunosuppressive regime - Fluschnik, Nina (BMJ Publishing Group, 2014)
We report on a challenging case of a 34-year-old male patient with giant cell myocarditis (GCM) and fulminant relapse after discontinuing immunomodulatory therapy 2 years after the initial event. Specific combined immunosuppressive therapy with antithymocyte globulin (ATG), cyclosporine and high-dose glucocorticoids combined with guideline-based heart failure medication led to the recovery of GCM, improvement of systolic left ventricular function and clinical remission. This case report emphasises the importance of an immunosuppressive therapy for the prognosis and outcome and the risk of discontinuation. Most importantly, ATG seems to be one new possible potential treatment option for patients with acute GCM.